2006
DOI: 10.1200/jco.2006.24.18_suppl.18002
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of erlotinib given daily for patients with metastatic melanoma (MM)

Abstract: 18002 Background: Erlotinib is a small molecule tyrosine kinase inhibitor (TKI) that targets epidermal growth factor receptor (EGFr). The EGFr is a potential therapeutic target because it is expressed by a number of malignancies, including melanocytic lesions, and in some plays an important role in the biology of the cancer. Our aim was to conduct a phase II study evaluating erlotinib in patients (pts) with measurable metastatic melanoma. Methods: Eligibility criteria included measurable disease, ECOG PS = 0–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Initial clinical trials of imatinib for metastatic melanoma were disappointing. There was no objective response or disease progression at 6 months in groups of 16 and 26 patients (Ugurel et al, 2005;Wyman et al, 2006), despite positivity for KIT protein in most melanomas in the first group. However, an anecdotal report described a major response in one patient with a mucosal melanoma containing mutant KIT (Lutzky et al, 2008).…”
Section: Kit In Melanomamentioning
confidence: 84%
See 1 more Smart Citation
“…Initial clinical trials of imatinib for metastatic melanoma were disappointing. There was no objective response or disease progression at 6 months in groups of 16 and 26 patients (Ugurel et al, 2005;Wyman et al, 2006), despite positivity for KIT protein in most melanomas in the first group. However, an anecdotal report described a major response in one patient with a mucosal melanoma containing mutant KIT (Lutzky et al, 2008).…”
Section: Kit In Melanomamentioning
confidence: 84%
“…However, treatment with another EGFR inhibitor, erlotinib, did not affect melanoma cell proliferation although there was inhibition of MAPK and AKT signalling pathways (Schicher et al., 2009). Moreover, in a phase II clinical study, erlotinib (150 mg daily) was preliminarily reported to have minimal or no single‐agent activity against metastatic melanoma (Wyman et al., 2006). A recent study also found that increased ERBB3 expression is a marker of poor prognosis in melanoma, with frequent high expression in melanoma and no expression in normal melanocytes (consistent with the above phospho‐array findings).…”
Section: Functions and Alterations Of Specific Rtks In Melanomamentioning
confidence: 99%
“…The role of inhibitors of ckit in these subtypes is under evaluation (50). A phase II trial of erlotinib in 14 patients showed no responses (51).…”
Section: Growth Factor Receptorsmentioning
confidence: 99%